Corpses and Capital: Narratives of Gendered Violence in Two Costa Rican Novels - Laura Barbas Rhoden (Studies in 20th & 21st Century Literature, 2008)
In a region prone to violence and political corruption, Costa Rica has been touted as an ecological paradise, a stable democracy, and an egalitarian society. However, Costa Rican fiction from the late twentieth century contests this idyllic image and presents instead a world of intrigue, violence, and criminality. El año del laberinto (2000) by Tatiana Lobo and Cruz de olvido (1999) by Carlos Cortés are two novels that serve as an excellent introduction to developments in postwar fiction and scholarship from Central America. In my analysis, I first situate the novels in the context of Central American cultural and political developments in recent decades and then consider the linking of narrative, gender, and violence in the novels. My study centers on the authors' use of crime to challenge national myths and to deconstruct narratives that have been instrumental in constructing cherished national identities. Of particular importance is the depiction of gendered bodies and the violence practiced upon them, as well as the politics surrounding bodies and violence in national narratives and in the authors' contemporary stories.
Keywords: violence; gender; gendered violence; Cosa Rica; El año del laberinto; Tatiana Lobo; Cruz de olvido; Carlos Cortés; postwar fiction; narrative